HUMAN ORGAN TRAFFICKING – THE “YELLOW HOUSE” CASE (Heritage, 2026)
This paper examines the case of human organ trafficking known as the “Yellow House” through a multidimensional and multidisciplinary lens, placing it at the intersection of war crimes, organized crime, and long-term security challenges in the Western Balkans. The relevance of this topic is rooted in the long-standing and complex nature of Serbian–Albanian relations, as well as in the specific conditions that emerged during the armed conflicts of the late 1990s in Kosovo and Metohija. In this context, missing persons, detained civilians, and wounded combatants were exposed to heightened vulnerability, which organized criminal networks were able to exploit. The “Yellow House” case illustrates how wartime structures did not simply disappear after the conflict, but in certain instances evolved into criminal networks pursuing financial gain alongside broader political and strategic objectives.The theoretical framework of the paper draws on organized crime theory and on concepts of wartime and post-conflict transformation. This framework enables an analysis of hierarchical structures and the gradual integration of elements of former paramilitary formations into organized criminal networks. Such an approach makes it possible to better understand how instability created by armed conflict can be instrumentalized for illicit activities, including human organ trafficking, and how these practices generate long-term security risks for local communities and the region as a whole.From a methodological perspective, the study relies on qualitative research, combining a case study approach with systematic content analysis of key documents and reports. Particular attention is given to the publicly available findings of Carla Del Ponte, the Dick Marty Report, as well as reports produced by international and local institutions involved in investigations and judicial proceedings. The central part of the paper focuses on the functioning of organ trafficking networks, addressing issues of logistics, geographic locations, victim identification, and the roles of specific actors. This allows for a more nuanced understanding of the organizational and operational dynamics underlying these criminal activities.The concluding section brings together the main findings of the analysis, emphasizing the complexity of human organ trafficking in post-conflict environments and the challenges it poses for the protection of human rights and the enforcement of international humanitarian law. By adopting a multidisciplinary approach, the paper seeks to contribute to discussions on both preventive and punitive responses and to provide a basis for further research on organized crime in wartime and post-conflict settings.
Keywords: organ trafficking, Yellow House, Kosovo Liberation Army, war crimes, organized crime.